TESTING BAYESIAN UPDATING WITH THE ASSOCIATED PRESS TOP 25. - STONE, DANIEL F. (Economic Inquiry, 2013)
Most studies of Bayesian updating use experimental data. This article uses a non-experimental data source-the voter ballots of the Associated Press college football poll, a weekly subjective ranking of the top 25 teams-to test Bayes' rule as a descriptive model. I find that voters sometimes underreact to new information, sometimes overreact, and at other times their behavior is consistent with estimated Bayesian updating. A unifying explanation for the disparate results is that voters are more responsive to information that is more salient (i.e., noticeable). In particular, voters respond in a 'more Bayesian' way to losses and wins over ranked teams, as compared to wins over unranked teams, and voters seem unaware of subtle variation in the precision of priors. ( JEL D80, D83, D84)